ТЕХНОЛОГИЯ ТАЪЛИМИДА ЎҚУВЧИЛАРНИ ХАЛҚ ҲУНАРМАНДЧИЛИГИ КАСБЛАРИГА ЙЎНАЛТИРИШНИ ТАКОМИЛЛАШТИРИШ - Шомирзаев, М.Х. (SCIENCE and SOCIETY, 2020)
The article describes the content of interdisciplinary improvement of the spectral-variable components os folk crafts in school technology education.